2000
DOI: 10.1080/073993300300340529
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Attitudes, Knowledge, and Screening Behavior in Women With and Without a Family History of Breast Cancer

Abstract: Women volunteers with or without a first-degree relative with breast cancer (FDR) were compared on several measures. Relative to the comparison group, women in the FDR group had more negative attitudes about breast cancer (including more anxiety about breast cancer), viewed their risk for getting breast cancer as greater (although they underestimated the actual risk), and were more likely to engage in appropriate screening behavior. A high percentage of women in both groups stated that they would want to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 9 publications
(16 reference statements)
1
12
1
Order By: Relevance
“…Women also described the contribution of this experiential knowledge to their perceptions of their own breast cancer risk. This sense of vulnerability to breast cancer among women with a family history and the key role of experiential knowledge in shaping perceived risk has been reported in other studies (Andersen et al, 2003;Hailey et al, 2000;Sivell et al, 2008).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Women also described the contribution of this experiential knowledge to their perceptions of their own breast cancer risk. This sense of vulnerability to breast cancer among women with a family history and the key role of experiential knowledge in shaping perceived risk has been reported in other studies (Andersen et al, 2003;Hailey et al, 2000;Sivell et al, 2008).…”
Section: Discussionsupporting
confidence: 76%
“…These experiences were clearly impactful, demonstrated by the highly emotive language used to describe them. These experiences also led many women to see breast cancer as a threat to themselves, as has been demonstrated in other studies reporting increased perceived risk, as well as increased cancer anxiety and intrusive thoughts among women with close personal experiences of breast cancer (Andersen et al, 2003;Hailey et al, 2000).…”
Section: Discussionmentioning
confidence: 76%
“…Relative to women without a FH of BC, prior research suggests women with a FH of BC tend to report inaccurately high perceptions of personal BC risk and greater anxiety and distress, particularly in BC screening settings (Brain, Norman, Gray, & Mansel, 1999; Erblich, Bovbjerg, & Valdimarsdottir, 2000; Hailey, Carter, & Burnett, 2000). However, in our study, BBB-related distress ratings for women without a FH of BC consistently exceeded the distress ratings for women with a FH, suggesting no FH of BC may be a risk factor for distress in the BBB setting.…”
Section: Discussionmentioning
confidence: 99%
“…As such, FHH information is relevant to all family members, making it particularly useful in family-based interventions. Although FHH information has been underutilized in medicine (Berg et al, 2009), research has shown that provision of FHH information is associated with improved health behaviors including physical activity (Ruffin et al, 2011), nutritional intake (Pijl et al, 2009; Ruffin et al, 2011), and cancer screening (Hailey, Carter, & Burnett, 2000). Wang et al (2015) further provided insight into how provision of FHH-based risk information may lead to health behavior change.…”
Section: Family Health History Information For Family-based Interventmentioning
confidence: 99%